Zgodovina raziskovanja plazme - Južnič, Stanislav (Vakuumist, 1998)
The desription of the scientific research in plasma physics from the first notions in chatode ray tube, until the modern approaches to the fusion reactors is given. First part of the articles describes the beginning of plasma physics among researches of low pressure discharges.
Keywords: fizika plazme; plazma; zgodovinski pregledi